Bioactives and Functional Ingredients in Foods - Pacifico, Severina; Piccolella, Simona (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The close relationship between food intake and health promotion is not new; it dates back to Hippocrates's famous "let food be your medicine and medicine be your food", which is still as timely as ever. In recent years, some scientific evidence has supported this statement, showing that dietary plant extracts, or bioactive compounds isolated therefrom, are able to prevent or slow down the progression of chronic and degenerative diseases, making them particularly interesting from a nutraceutical point of view. On the other hand, extensive chemical investigations of functional plant extracts' constituents are needed to rationalize certain bioactivity, in terms of efficacy and safety.